Cultural aspects of sustainability challenges of island-like territories: case study of Macau, China - Ivan Zadori (Ecocycles, 2016)
Sustainability challenges and reactions are not new in the history of human communities but there is a substantial difference between the earlier periods and the present situation: in the earlier periods of human history sustainability depended on the geographic situation and natural resources, today the economic performance and competitiveness are determinative instead of the earlier factors. Economic, social and environmental situations that seem unsustainable could be manageable well if a given land or territory finds that market niche where it could operate successfully, could generate new diversification paths and could create products and services that are interesting and marketable for the outside world. This article is focusing on the sustainability challenges of Macau, China. The case study shows how this special, island-like territory tries to find balance between the economic, social and environmental processes, the management of the present cultural supply and the way that Macau creates new cultural products and services that could be competitive factors in the next years.